Vitamin D Deficiency is not Associated with Higher Levels of SYNTAX Score - Cerit,Levent (2019)
Abstract Objective: To evaluate the association between serum vitamin D (vitD) level and SYNTAX (synergy between percutaneous coronary intervention with taxus and cardiac surgery) score (SS). Methods: The medical records of consecutive patients, who underwent coronary artery bypass graft surgery, were retrospectively reviewed. The study group consisted of 158 patients. Biochemical, clinical, and echocardiographic parameters and SS were evaluated in all patients. The patients were divided into 2 groups according to SS (≥23= high, <23= low). Results: The high SYNTAX score (HSS) group was older and had higher body mass index, C-reactive protein (CRP), low-density lipoprotein, and fasting plasma glucose level than the low SYNTAX score (LSS) group. The HSS group had lower high-density lipoprotein and vitD level than the LSS group. The HSS group had a higher prevalence of diabetes mellitus (DM), hypertension (HT), hyperlipidemia (HL), and current smoking patients than the LSS group. On univariate analysis, age, HT, DM, HL, smoking, CRP, and serum vitD level were associated with HSS. On multivariate analysis, HT, DM, and HL were independent predictors of HSS (odds ratio [OR]: 2.137, 95% confidence interval [CI]: 1.468-2.935, P<0.001; OR: 3.559, 95% CI: 2.763-5.927, P<0.001; OR: 2.631, 95% CI: 1.529-3.438, P<0.001; respectively). Conclusion: In our study, we have found out that HT, DM, and HL were independent predictors of HSS. Serum vitD level was not found to be an independent predictor of HSS.